Greening the Greyfields New Models for Regenerating the Middle Suburbs of Low-Density Cities - Newton, Peter W; Newman, Peter; Glackin, Stephen; Thomson, Giles (Palgrave Macmillan, 2021)
This open access book outlines new concepts, development models, governance and implementation processes capable of addressing the challenges of transformative urban regeneration of cities at precinct scale.